Identifying potential emerging human rights implications in Chinese smart cities via machine-learning aided patent analysis - Joss Wright; Valentin Weber; Gregory Walton (Internet Policy Review, 2023)
In this work, we investigate smart city technologies primarily through an examination of trends in patent filing. We apply machine learning methods both to explore the increasing rates of patent filing globally for smart city technologies, and also to identify the emerging topics on which companies are choosing to focus their efforts. We focus particularly on deployed and emerging urban systems-of-systems in China, which represent a high proportion of patents filed for smart city technologies, with a view to their potential global impacts. As a leading source of innovation in the development of smart cities, Chinese patent filing exerts significant influence on similar technologies adopted globally. Our global patent analysis highlights emerging trends in smart city innovations, and the increased adoption of technologies and processes that present significant human rights concerns, especially concerns to privacy, freedom of expression, and assembly.
Keywords: 300; Smart cities; Human rights; China; Machine learning; Patents